Aula do corpo - Noronha, Rodrigo de Azevedo (2010)
This study discusses the participation of the body in the cognitive process in a regular school, more specifically about classes for children of seven and eight year old, age group that the author has specialized with its entitled Body Classes. The text contrasts the content contained in the Brazilian National Curriculum Standards offered by the Ministry of Culture and Education to the content involved in this Body Classes. Then it discusses the multiplicity of meanings that involve the word body and how they can be interwoven with education in the formatting of a student to serve the dominant interests. The study goes on to ask questions and suggest new possibilities of ideas about the body in class, stressing the importance of emotions and feelings in the cognitive process. It is based on recent neurobiological findings, specifically with Humberto Maturana and Antonio Damásio, who put the live - body in the genesis of thought. These studies question the extent of rationality of the Cartesian thinking when they suggest not a separation (substance dualism), but an inevitable interaction between mind and body. This study is also in the thoughts of Edgar Morin and his pedagogy for the future that contrasts the Complex to the Cartesian thought and also discusses the pedagogical function of formatting of the student in schools that invest in a mentalist and competitive education. Finally, the study presents its own fragility